Evaluating User Experience (UX) of the Top E-commerce Websites in Malaysia: A Quantitative Study - Layla HASAN (Communications of International Proceedings, 2022)
The continuous growth in online shopping globally requires owners of e-commerce websites to ensure that their websites have positive user experience, to increase their sales and their competitiveness. This research evaluated the user experience of the top three most visited e-commerce websites in Malaysia: Shopee, Lazada, Pgmall using questionnaire method. The questionnaire was developed based on specific criteria that was suggested in this research to evaluate user experience of any e-commerce website. The criteria consist of 27 metrics to evaluate utilitarian features and 13 metrics to evaluate hedonic features of any e-commerce website. Quantitative and qualitative data was collected from the questionnaire. The quantitative results obtained from the analysis of the questionnaire identified seven user experience problems (6 utilitarian issues and one hedonic issue) on the tested websites. The qualitative results obtained from the analysis of the questionnaire identified 22 user experience problems on the tested websites; these related to 12 utilitarian features and 10 hedonic features. This research recommends considering 12 utilitarian features and 10 hedonic features while developing e-commerce website in order to achieve positive user experience on e-commerce websites.
Keywords: User experience; e-commerce; Malaysia; utilitarian; hedonic.